Nanoporous chromium thin film for active detection of toxic heavy metals traces using surface-enhanced Raman spectroscopy - Ashour M Ahmed; Mohamed Shaban (Materials Research Express, 2020)
In this work, nanoporous Cr thin film was designed by a novel method for the detection of toxic heavy metals based on surface-enhanced Raman spectroscopy. Nanoporous Cr thin film has been deposited on an aluminum substrate through a developed etching/DC electrodeposition technique of the hexagonal porous anodic alumina (PAA) template/Cr nanoparticles, respectively. The structures and morphologies of the fabricated samples were investigated by different characterization tools. The FE-SEM illustrates nanoporous Cr particles of rough surfaces and different sizes are formed on the Al substrate. Also, there are ultrafine Cr nanoparticles covered the surface of the Cr nanoporous film that can act as hot-spots during the detection of heavy metal ions. The proposed sensor established high selectivity at low concentrations between different heavy metal ions (Pb ^2+ , Hg ^2+ , Cd ^2+ ). Also, it showed excellent selectivity towards Pb ^2+ over the other metal ions. Hence, this category of sensors could be applied for sensitive determining of Pb ^2+ , Hg ^2+ , Cd ^2+ in contaminated water.